In Planta Functional Analysis and Subcellular Localization of the Oomycete Pathogen Plasmopara viticola Candidate RXLR Effector Repertoire - Liu, Yunxiao; Lan, Xia; Song, Shiren; Yin, Ling; Dry, Ian B.; Qu, Junjie; Xiang, Jiang; Lu, Jiang (Frontiers in Plant Science, 2018)
Abstract Downy mildew is one of the most destructive diseases of grapevine, causing tremendous economic loss in the grape and wine industry. The disease agent Plasmopara viticola is an obligate biotrophic oomycete, from which over 100 candidate RXLR effectors have been identified. In this study, 83 candidate RXLR effector genes (PvRXLRs) were cloned from the P. viticola isolate "JL-7-2" genome. The results of the yeast signal sequence trap assay indicated that most of the candidate effectors are secretory proteins. The biological activities and subcellular localizations of all the 83 effectors were analyzed via a heterologous Agrobacterium-mediated Nicotiana benthamiana expression system. Results showed that 52 effectors could completely suppress cell death triggered by elicitin, 10 effectors could partially suppress cell death, 11 effectors were unable to suppress cell death, and 10 effectors themselves triggered cell death. Live-cell imaging showed that the majority of the effectors (76 of 83) could be observed with informative fluorescence signals in plant cells, among which 34 effectors were found to be targeted to both the nucleus and cytosol, 29 effectors were specifically localized in the nucleus, and 9 effectors were targeted to plant membrane system. Interestingly, three effectors PvRXLR61, 86 and 161 were targeted to chloroplasts, and one effector PvRXLR54 was dually targeted to chloroplasts and mitochondria. However, western blot analysis suggested that only PvRXLR86 carried a cleavable N-terminal transit peptide and underwent processing in planta. Many effectors have previously been predicted to target organelles, however, to the best of our knowledge, this is the first study to provide experimental evidence of oomycete effectors targeted to chloroplasts and mitochondria.